1985
DOI: 10.1149/1.2113845
|View full text |Cite
|
Sign up to set email alerts
|

Chromium‐Doped Raney Nickel Catalyst for Hydrogen Electrodes in Alkaline Fuel Cells

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 3 publications
(7 reference statements)
3
25
0
Order By: Relevance
“…Using MA it has been possible to synthesize novel materials with special physical and chemical properties. By the other hand, nickel is a relatively inexpensive and highly active non-noble metal catalyst convenient for developing hydrogen electrodes to be used in alkaline fuel cells [4]. Sturm [5] and Mund et al [6] found that its catalytic activity was enhanced by additions of transition metals such as titanium, iron and molybdenum.…”
Section: Introductionmentioning
confidence: 99%
“…Using MA it has been possible to synthesize novel materials with special physical and chemical properties. By the other hand, nickel is a relatively inexpensive and highly active non-noble metal catalyst convenient for developing hydrogen electrodes to be used in alkaline fuel cells [4]. Sturm [5] and Mund et al [6] found that its catalytic activity was enhanced by additions of transition metals such as titanium, iron and molybdenum.…”
Section: Introductionmentioning
confidence: 99%
“…The test layer is a Raney nickel layer, the concentration polarization in which is to be measured. The load current is sustained by the working layer which is catalyzed with 0.4% chromium-doped Raney nickel (6). Use of this catalyst not only lowers the polarization loss of the working layer, but also stabilizes its polarization characteristics, thereby providing more accurate and reproducible polarization data for the test layer.…”
Section: Cell Arrangement and Polarization Measurement--thementioning
confidence: 99%
“…Chromium-doped Raney nickel catalyst.--The catalytic activity of Raney nickel is enhanced by doping a small amount of chromium (6). Figure 11 shows ~o -~ vs. thickness plots for the hydrogen electrodes catalyzed with this Raney nickel.…”
Section: Raney Nickel Hydrogen Electrodes 1587mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Raney nickel has excellent hydrogen adsorption ability and relatively large surface area, some disadvantages have also been reported, such as high electrolyte diffusion resistance due to low pore volume and small pore size [98,99], and insufficient conductivity [97]. One type of mitigation is to support Raney nickel on carbon blacks, which will decrease its electrolyte diffusion resistance and increase its electrical conductivity [97].…”
Section: Raney Nickelmentioning
confidence: 99%